Silence and Human Development - Olearczyk, Teresa (Paedagogia Christiana, 2020)
This article seeks to answer a fundamental question: What has made silence a scarce commodity, even though it is among the more important human needs? The impact of silence on human development over the course of a lifetime, and in relationships with others, is shown. The affirmative aspects of silence from an anthropological perspective, as a natural human need that contributes to the development of full humanity, is underlined. With this aim, the article clarifies the differences between silence in the sense of quiet hush, and in the sense of keeping quiet; and between solitude and loneliness. The paper concentrates on the positive influence of silence on personality development and purposely omits the negative aspects of silence, since they do not serve the integral development of the person – this issue needs a separate discussion.